PSYCHOLOGICAL STRESS AND ITS ROLE IN THE PRECIPITATION OF ANGINA PECTORIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Psychological stress has been increasingly recognized as a significant contributor to cardiovascular morbidity, yet its specific role in precipitating angina pectoris episodes remains inadequately characterized in clinical practice. Understanding this relationship is essential for comprehensive cardiovascular risk management and therapeutic intervention. Methods: A cross-sectional analytical study was conducted among 248 patients diagnosed with stable angina pectoris attending the cardiology outpatient department. Psychological stress was assessed using the Perceived Stress Scale (PSS-14) and the Depression Anxiety Stress Scales (DASS-21). Angina characteristics were evaluated using the Seattle Angina Questionnaire (SAQ) and patient-reported episode frequency. Correlation analyses, independent t-tests, and multiple regression analyses were performed. Results: Patients with high perceived stress (PSS-14 score ≥28) demonstrated significantly greater weekly angina episode frequency (4.82 ± 1.94 vs. 2.31 ± 1.12, p